Biomass Energy in Malaysia: Current Scenario, Policies, and Implementation Challenges - Rashidi, N.A. (Springer, 2022)
The energy demand in Malaysia has shown a dramatic increase over the last few years: with natural gas and coal being the primary contributors. Nevertheless, due to declining in fossil fuel reserves coupled with negative environmental impacts, shifting to sustainable renewable energy for meeting the future energy demand is recommended. Since Malaysia is rich with natural resources, utilization of biomass energy (bioenergy/biofuel) as the alternative energy is promising to be further explored. Therefore, this review paper intents to discuss the current scenario of different types of biomass energy in Malaysia along with the up-to-date local biomass energyârelated environmental policy (from 2016 onwards). In addition, challenges and barriers for large-scale implementation of the biomass energy in Malaysia are to be discussed. Overall, this review paper is interesting as it can assist in promoting the biomass utilization as energy source, and to ensure the future growth of biomass energy market in the country along with its effective implementation while alleviating poor disposal problem and to create job employment opportunities. Furthermore, a collective effort to expand potential biomass feedstocks, apart from oil palm, should be emphasized to encourage the renewable energy production diversification in the nation. Â© 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.